Oxybelus lusitanicus spec. nov., a new Crabronid wasp species from Portugal - Cross, Ian (Zootaxa, 2020)
Oxybelus lusitanicus spec. nov., a new European Crabronid wasp species is described and diagnosed. It is currently known only from two regions of Portugal. An amendment to the relevant section of Guichard’s (1993) most recent English language key to European Oxybelus Latreille, 1796 is included.